Point-of-Care Ultrasonography in the Diagnosis of Retinal Detachment, Vitreous Hemorrhage, and Vitreous Detachment in the Emergency Department - Lahham, Shadi (JAMA Netw Open, 2019)
IMPORTANCE: Ocular symptoms represent approximately 2% to 3% of all emergency department (ED) visits. These disease processes may progress to permanent vision loss if not diagnosed and treated quickly. Use of ocular point-of-care ultrasonography (POCUS) may be effective for early and accurate detection of ocular disease. OBJECTIVE: To perform a large-scale, multicenter study to determine the utility of POCUS for diagnosing retinal detachment, vitreous hemorrhage, and vitreous detachment in the ED. DESIGN, SETTING, AND PARTICIPANTS: A prospective diagnostic study was conducted at 2 academic EDs and 2 county hospital EDs from February 3, 2016, to April 30, 2018. Patients who were eligible for inclusion were older than 18 years; were English- or Spanish-speaking; presented to the ED with ocular symptoms with concern for retinal detachment, vitreous hemorrhage, or vitreous detachment; and underwent an ophthalmologic consultation that included POCUS. Patients with ocular trauma or suspicion for globe rupture were excluded. The accuracy of the ultrasonographic diagnosis was compared with the criterion standard of the final diagnosis of an ophthalmologist who was masked to the POCUS findings. Seventy-five unique emergency medicine attending physicians, resident physicians, and physician assistants performed ocular ultrasonography. EXPOSURE: Point-of-care ultrasonography performed by an emergency medicine attending physician, resident physician, or physician assistant. MAIN OUTCOMES AND MEASURES: Sensitivity and specificity of POCUS in identifying retinal detachment, vitreous hemorrhage, and vitreous detachment in patients presenting to the ED with ocular symptoms. RESULTS: Two hundred twenty-five patients were enrolled. Of these, the mean age was 51 years (range, 18-91 years) and 135 (60.0%) were men; ophthalmologists diagnosed 47 (20.8%) with retinal detachment, 54 (24.0%) with vitreous hemorrhage, and 34 (15.1%) with vitreous detachment. Point-of-care ultrasonography had an overall sensitivity of 96.9% (95% CI, 80.6%-99.6%) and specificity of 88.1% (95% CI, 81.8%-92.4%) for diagnosis of retinal detachment. For diagnosis of vitreous hemorrhage, the sensitivity of POCUS was 81.9% (95% CI, 63.0%-92.4%) and specificity was 82.3% (95% CI, 75.4%-87.5%). For vitreous detachment, the sensitivity was 42.5% (95% CI, 24.7%-62.4%) and specificity was 96.0% (95% CI, 91.2%-98.2%). CONCLUSIONS AND RELEVANCE: These findings suggest that emergency medicine practitioners can use POCUS to accurately identify retinal detachment, vitreous hemorrhage, and vitreous detachment. Point-of-care ultrasonography is not intended to replace the role of the ophthalmologist for definitive diagnosis of these conditions, but it may serve as an adjunct to help emergency medicine practitioners improve care for patients with ocular symptoms.